Comparação do desempenho motor de crianças entre escolas públicas de tempo parcial e integral - Bim, Ricardo Henrique (2013)
The purpose of this study was to compare the motor performance of children enrolled in full time and part time public schools. In this study, causal feature comparison, involved 159 children (77 part teaching and 82 full teaching) of both sexes, aged 7 and 8 years old, enrolled in the 3rd. year of elementary teaching from four public schools in the municipal network of Maringá city, Paraná state. The measuring instruments used were the Test of Gross Motor Development-2 (TGMD-2) and the Movement Assessment Battery for Children-2 (MABC-2). Data collection occurred in the first half of 2012 at the school in which each child was studying, where they were evaluated according to the test protocols. For quantitative data analysis it was used descriptive statistics, Kolgomorov-Smirnov normality test and Mann Whitney U test, adopted significance of P≤0.05. The results showed that the difficulty of movement was significantly more evident in public school children integral-time, in which the rate of DCD was 2.5% and at risk of difficulty was 19.5%. Among public school children part time, none were diagnosed with DCD and 14.3% showed risk of difficulty in movement. The motor performance in the MABC-2 of part-time school's children was higher compared to the performance of full-time school's children (p = 0.030). Differences were observed in motor ability to aiming and catching (p = 0.020) and in the task of throwing beanbag on to mat (p = 0.016) and hope on mat (0.041). In TGMD-2 it was found that 92.2% of children of school part-time motor performance were below average by the proposed test. Among children in school full-time this percentage was 85.3%. However, the percentage of children in school full-time identified with motor development was considered very poor (19.5%) and in school children of part-time it was 9.1%. In both groups, no child reached motor performance above average, superior or very superior, corroborating other studies with Brazilian children. There was no difference in motor performance in general score of TGMD-2 school children part-time in comparison to the performance of school children full time. Significant difference was noted only in the motor skill of striking (p = 0.008), in which part-time school's children were higher, and the ability to kicking (p = 0.000), in which integral-time school's children were best. We conclude that full-time public school's children did not show higher motor performance when compared to the part-time public school's children, suggesting that the integral time school and its complementary activities are not enough to improve motor development of children. Finally, leaders and educators must articulate to organize and implement the actions necessary for the success of these programs.